The Covid-19 pandemic and the effects on the collection and distribution of Fethab in the municipalities of Mato Grosso - Oliveira Pedroso Gil, Alessandra; Franco, Cleiton; Beato Ximenes de Melo, Sonia Aparecida; Guzatti, Nataliê Christy; Rodrigues Figueiredo, Adriano Marcos (Revista de Negócios, 2024)
The economic repercussions caused by Covid-19 generated an abrupt drop in supply and demand in most economic activities and signs of recession worldwide. World Bank projections in 2020 show the effects of the Covid-19 pandemic, causing a 5.2% reduction in world growth in 2020. Agribusiness, through commodity exports, positively affected the Brazilian trade balance. The objective of this work was to measure the effects of the Covid-19 pandemic on the collection and distribution of State Fund for Transportation and Housing (FETHAB - Fundo Estadual de Transporte e Habitação) in the municipalities of Mato Grosso. The methodology used was the differences-in-differences model, with a cut-off from the beginning of the records of Covid-19 cases in Mato Grosso. The monthly data panel for the municipalities of Mato Grosso was built using information from the FETHAB resources extracted from the electronic address of the Secretariat of Finance of the State of Mato Grosso (SEFAZ/MT) for the period from 2019 to 2021, together with monthly export data (Siscomex) and prices (Conab). The results show that there was a 37% increase in exports. This also raised commodity prices by 73% for soybeans and 83% for a bag of corn. As a result of the increase in exports, there was also an improvement in the FETHAB collection and distribution of around 11%. The devaluation of the real against the dollar and the increase in demand for food caused an increase in prices and exports and, consequently, an improvement in the collection and distribution of FETHAB to the municipalities of Mato Grosso.